Cooking and eating in renaissance Italy : from kitchen to table / Katherine A McIver - McIver, Katherine A.
"This is the story of cooking and eating. It is about the experience of dining and the orchestration of a meal in Renaissance Italy. We'll move from the kitchen, to the acquisition of goods, to food preparation and final presentation at the table, both in the city residence and the country estate....Our story begins in the late-medieval kitchen, dating from the late fourteenth to the early fifteenth century...then turns its focus to the Renaissance, the late fifteenth through the sixteenth century...and ends in the 1660s...."